Correlation of Metabolomics and Functional Foods Research in 2020 to 2023: Bibliometric Analysis - Dewi, Nazmah Sefriani (ASEAN Journal for Science and Engineering in Materials, 2025)
This research was conducted to determine the development of research on metabolomics and functional food using bibliometric analysis including analysis of top citations, and publishers, visualization of the most productive authors, and a map of publication development based on keywords. This research method is descriptive quantitative with bibliometric analysis using Publish or Perish software for data collection and VOSviewer to visualize related research terms. Data collection was carried out by searching the Google Scholar database with the keywords "metabolomics" and "functional food" in the period 2020 to 2023. The research results show that research on metabolomics and functional food continues to increase. Analysis of the journals with the highest citations were 17 journals, the majority of which were published by Elsevier. The visualization results obtained 11 clusters and it was found that the most researched subjects were "metabolomics", "metabolome", and "health" with researchers Wang, Liu, and Li identified as the most productive authors on this topic. It is hoped that this research can help researchers determine the focus of their research and become a reference for further research.